The Effect of Financial Performance on Value Company (Dividend Policy as A Moderating Variable) in Manufacturing Companies on The Indonesia Stock Exchange - Tommy Kristian Catur Nugroho; Muhammad Nurdin; Tusiana Dewi (Hut Publication Business and Management, 2023)
The purpose of this study was to determine and analyze the INFLUENCE OF FINANCIAL PERFORMANCE ON COMPANY VALUE (DIVIDEND POLICY AS A MODERATING VARIABLE) IN MANUFACTURING COMPANIES IN THE INDONESIA STOCK EXCHANGE simultaneously and partially. on Devuden Policy in Manufacturing companies listed on the Indonesia Stock Exchange and analyzing which variables among the Liquidity Profitability Leverage variables have the dominant influence on company value in mining companies listed on the Indonesia Stock Exchange. This study used a quantitative research approach, where this quantitative approach required numerical data which were analyzed using multiple linear regression analysis using the SPSS program to test a number of hypotheses. The ratios used in this study are profitability ratios (Return On Assets/ROA) and liquidity ratios (Current Ratio/CR). The results of the study show that the results of simultaneous testing of the independent variables, namely working capital turnover, liquidity, capital structure and company size have an effect on the profitability of mining companies listed on the Indonesia Stock Exchange. The results of the partial test show that the independent variable is Liquidity, Profitability, Leverage on company value in Manufacturing companies listed on the Indonesia Stock Exchange.